KEGIATAN PENDAMPINGAN PENERAPAN TIK PADA NEXT GEN’S PARTY KOI SHOW KE 2 - Budi Suyanto; Mangaras Y F; Wilis Kaswidjanti; Dessyanto Boedi P; Nur Heri Cahyana (Pusat Riset dan Inovasi Nasional, 2023)
Inspection and implementation of ICT in competition management at Next Gen's Party Koi Show #2. Training with two-way interaction methods, presentations and exercises on how to use the activity registration application and back office application to manage activity participants and provide support on activity days. Next Gen's Party Koi Show #2 Online Registration Application Install Next Gen's Party Koi Show #2 Back Office Online Application Install Next Gen's Party Koi Show #2 Participant Registration Support Activities Next Gen Support Committee Party Koi Show #2 activities in Participant management.